PENDIDIKAN KARAKTER KRISTIANI YANG DIBERKATI: MENGARTIKAN MATIUS 5:6-12 DALAM KEHIDUPAN KONTEMPORER - Nelsi Malisan; Resi Mangampa; Mersi Suba (CV. ADIBA AISHA AMIRA, 2023)
This research aims to investigate the implementation and meaning of Christian character education based on the teachings in the Gospel of Matthew 5:6-12 in the context of contemporary life. The research methodology employed is qualitative literature review, involving the analysis of Biblical texts, theological literature, and scholarly studies related to Christian character education. The study identifies and analyzes the core values contained in the teachings of Matthew 5:6-12, namely humility, compassion, purity of heart, peace, and steadfast faith. Furthermore, the research examines the relevance and application of these values in the modern context, including the challenges and opportunities faced by Christian individuals in their efforts to cultivate a blessed character. The findings of the research indicate that the teachings of Matthew 5:6-12 provide a strong foundation for Christian character education that focuses on the development of virtues, attitudes, and behaviors that reflect Christian values in everyday life. The study also identifies various strategies and approaches to character education that can be applied in the contemporary context. This research contributes significantly to the understanding of how the teachings of Matthew 5:6-12 can be applied in the context of modern Christian character education. The findings of this research are expected to serve as a source of inspiration and guidance for education practitioners, church leaders, and Christian individuals in their efforts to cultivate a blessed character in accordance with the teachings of Christ.